Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M110 - Julia Haberkern; Till J J Hanebuth (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Kongsberg EM122 multibeam echosounder during the RV METEOR cruise M110 GALIMOS (Monitoring the interaction between Oceanographic elements and Sedimentary seabed structures at the GALIcian margin). The cruise took place between 2014-09-15 and 2014-09-30 (Vigo, Spain – Cádiz, Spain), aiming to monitor the relationship between oceanography and seabed at the continental margin off the northwest Iberian Peninsula. The EM122 echosounder was used throughout the whole cruise for mid- and deep-water mapping, while the EM710 echosounder collected data in shallow waters. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Sound velocity profiles (SVP) archived at BSH are part of this submission. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).